Pathogen exposure and chronic toxicity mechanisms of viable but non-culturable state to Caenorhabditis elegans - Hongfei Huang; Yiwei Cai; Tong Sun; Guiying Li; Po Keung Wong; Taicheng An (Ecotoxicology and Environmental Safety)
Pathogenic bacterial infections have become an increasingly severe problem, presenting a major global challenge. Pathogenic bacteria cannot be detected by conventional methods when present in a viable but non-culturable (VBNC) state, resulting in an increased risk of bacterial infection as they have the potential to resuscitate and regain pathogenicity under favorable conditions. In this study, a liquid infection model was used to assess the impact and toxicity mechanisms of both wild-type (WT) and VBNC Pseudomonas aeruginosa to Caenorhabditis elegans, examining the various changes in both bacteria and nematodes. Results showed that VBNC state bacteria inhibited the physiological functions of C. elegans and compromise their intestinal barriers. Specifically, the upregulation of oxidative stress-related genes increased the accumulation of reactive oxygen species and lipofuscin in C. elegans by 185.0 % and 69.5 %, respectively. This suggests that oxidative stress may constitute a significant cause of nematode mortality. Additionally, VBNC bacteria that invaded C. elegans exhibited an increase in bacterial resuscitation up to 92.6 %, resulting in an increase in virulence factors, as shown by the upregulation of virulence-associated genes. Despite being less virulent than WT bacteria, VBNC bacteria significantly affected C. elegans. Therefore, long-term monitoring of VBNC resuscitation is required in biological systems.